The effect of point mutations within the N-terminal domain of Mason-Pfizer monkey virus capsid protein on virus core assembly and infectivity - Wildová, Marcela; Hadravová, Romana; Stokrová, Jitka; Krízová, Ivana; Ruml, Tomás; Hunter, Eric; Pichová, Iva; Rumlová, Michaela (Virology, 2008)
Retroviral capsid protein (CA) mediates protein interactions driving the assembly of both immature viral particles and the core of the mature virions. Structurally conserved N-terminal domains of several retroviruses refold after proteolytic cleavage into a beta-hairpin, stabilized by a salt bridge between conserved N-terminal Pro and Asp residues. Based on comparison with other retroviral CA, we identified Asp50 and Asp57 as putative interacting partners for Pro1 in Mason-Pfizer monkey virus (M-PMV) CA. To investigate the importance of CA Pro1 and its interacting Asp in M-PMV core assembly and infectivity, P1A, P1Y, D50A, T54A and D57A mutations were introduced into M-PMV. The P1A and D57A mutations partially blocked Gag processing and the released viral particles exhibited aberrant cores and were non-infectious. These data indicate that the region spanning residues Asp50-Asp57 plays an important role in stabilization of the beta-hairpin and that Asp57 likely forms a salt-bridge with P1 in M-PMV CA.
Keywords: virion; bodová mutace; Masonův-Pfizerův opičí virus; Virion; sestavení viru; Virus Assembly; Mason-Pfizer monkey virus; virové plášťové proteiny; Capsid Proteins; Point Mutation